2021
DOI: 10.1158/1538-7445.am2021-ct019
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT019: A phase I trial of the combination of the dual RAF-MEK inhibitor VS-6766 and the FAK inhibitor defactinib: Evaluation of efficacy in KRAS mutated NSCLC

Abstract: Background KRAS is a known oncogenic driver in non-small cell lung cancer (NSCLC), with KRAS G12C and G12V mutations occurring in ~13% and ~7% of the of NSCLC ( adenocarcinoma subtype). The dual RAF-MEK inhibitor VS-6766 has shown single agent activity against G12V KRAS mutated NSCLC (Guo C et al Lancet Oncology 2020, 21:1478-88). Based on pre-clinical data, we hypothesised that augmented focal adhesion kinase (FAK) signalling is a mechanism of resistance to MEK inhibition and devised the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…91 Beyond MEK inhibition, negative clinical trial results have been observed from RAS-selected trials assessing inhibitors of the synthetic lethality target, CDK4. [92][93][94][95] However, some cause for optimism remains, with the recently reported early clinical success of defactinib and VS-6766 (a dual RAF/MEK inhibitor) in KRAS G12V NSCLC, 96 as well as a vastly improved understanding of the contextual signaling outputs (and consequent vulnerabilities) conferred by mutations affecting different RAS isoforms, codons, and amino acids. 97,98 Underpinning all of the above is the paradigm-shifting success of immune checkpoint inhibitors in NSCLC, whose presence in monotherapy and combination regimens now anchor stages III-IV treatment guidelines.…”
Section: Moving Beyond Kras G12c Mutations In Lung Cancermentioning
confidence: 99%
“…91 Beyond MEK inhibition, negative clinical trial results have been observed from RAS-selected trials assessing inhibitors of the synthetic lethality target, CDK4. [92][93][94][95] However, some cause for optimism remains, with the recently reported early clinical success of defactinib and VS-6766 (a dual RAF/MEK inhibitor) in KRAS G12V NSCLC, 96 as well as a vastly improved understanding of the contextual signaling outputs (and consequent vulnerabilities) conferred by mutations affecting different RAS isoforms, codons, and amino acids. 97,98 Underpinning all of the above is the paradigm-shifting success of immune checkpoint inhibitors in NSCLC, whose presence in monotherapy and combination regimens now anchor stages III-IV treatment guidelines.…”
Section: Moving Beyond Kras G12c Mutations In Lung Cancermentioning
confidence: 99%
“…Therefore, this combination therapy is promising and is currently being tested in clinical trials for patients with several cancers, including KRAS-mutated NSCLC and LGSOC. In this phase I/II trial, the objective response rate to combination therapy was 15.0% in patients with KRAS-mutated NSCLC and 44.8% in patients with LGSOC 17,18,46,47 . Additionally, two ongoing phase II trials aim to evaluate the effectiveness of avutometinib and defactinib combination therapy in patients with KRASmutated NSCLC and in those with LGSOC 17,19,48 , and a useful biomarker is urgently needed for this combination therapy in patients with KRAS-mutated NSCLC.…”
Section: Discussionmentioning
confidence: 94%
“…However, its e cacy is limited owing to its side effects 45 . In contrast, combination therapy with avutometinib and defactinib was generally well-tolerated in a phase I trial (NCT03875820) 17,46 . Therefore, this combination therapy is promising and is currently being tested in clinical trials for patients with several cancers, including KRAS-mutated NSCLC and LGSOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal adhesion kinase (FAK) induction was identified as a potential resistance mechanism to VS-6766. Therefore, a combination phase I trial of VS-6766 and FAK inhibitor, defactinib, in NSCLC was performed, which resulted in an ORR of 15% and again showed activity in KRAS G12V-mutant NSCLC (2 out of 2 responses) [ 145 ]. Phase I and phase II studies involving VS-6766 in combinations with defactinib (NCT04620330 and NCT04625270), everolimus (NCT02407509), cetuximab (NCT05200442), adagrasib (NCT05375994), and sotorasib (NCT05074810) are planned or underway in multiple malignancies including lung, ovarian, and colorectal cancers.…”
Section: Downstream Signaling Inhibitionmentioning
confidence: 99%